Perlindungan Hukum Terhadap Anak Pasca Perceraian Orang Tua - Maesaroh, Siti (AL WASATH Jurnal Ilmu Hukum, 2024)
The results of this research are to find out what form of protection the law provides for children's rights after divorce, namely through preventive and repressive actions to provides confirmation to parents not to neglect their duties and obligations in fulfilling children's rights. If this right is not fulfilled properly and appropriately, the courts and competent legal institutions can impose sanctions and revoke parental rights for their negligence. In revoking parental rights, the child's obligations to the parents remain and do not change so that the parents are still obliged to fulfill them until the child grows up.